Maraviroc 150 mg daily plus lopinavir/ritonavir, a nucleoside/nucleotide reverse transcriptase inhibitor-sparing regimen for HIV-infected naive patients: 48-week final results of VEMAN study. (May 2015) - Nozza, S.; Galli, L.; Antinori, A.; Chiappetta, S.; Mazzotta, F.; Zaccarelli, M.; Ottou, S.; De Battista, D.; Pogliaghi, M.; Di Pietro, M.; Malnati, M.; Ripa, M.; et al.
Abstract: Non-conventional strategies with nucleoside/nucleotide reverse transcriptase inhibitor-sparing regimens in antiretroviral naive human immunodeficiency virus (HIV) -infected patients have been explored in clinical trials. A prospective, open-label, randomized (1:1), multicentre, proof-of-concept trial (VEMAN study, EUDRACT number 2008-006287-11) was conducted assigning HIV-infected naive patients to once-daily maraviroc plus lopinavir/ritonavir (MVC group) or to tenofovir/emtricitabine plus lopinavir/ritonavir (TDF/FTC group). Clinical and laboratory data were collected at baseline, and after 4, 12, 24, 36 and 48 weeks with the objective to evaluate the 48-week virological and immunological efficacy. HIV-1 DNA load and CD4 + T-cell subsets were analysed on frozen peripheral blood mononuclear cells collected at baseline, 4 and 48 weeks to explore the trend in HIV reservoirs. Fifty patients were randomized and included in the analysis. During follow up, HIV-1 RNA decreased similarly in both groups and, at week 48, all patients in the MVC group and 22/24 (96%) in the TDF/FTC group had < 50 copies/ml of HIV-1 RNA. CD4 + trend during follow up was higher in maraviroc-treated patients (MVC group: 286 (183–343) versus TDF/FTC group: 199 (125–285); Mann–Whitney U -test: p 0.033). A significant 48-week increase of CCR5 + CD4 + T cells and CD4 + effector memory cells was observed among maraviroc-treated patients (Wilcoxon signed rank test: p 0.016 and p 0.007, respectively). No significant variations were found in naive and central memory CD4 + T cells. Among naive patients with an R5 virus, treatment with maraviroc and lopinavir/ritonavir was shown to provide a virological response compared to a triple therapy and a greater immunological benefit.